Penerapan Relaksasi Diaphragmatic Breathing Exercise Terhadap Dyspnea Pada Asuhan Keperawatn Pasien Penyakit Paru Obstruktif (PPOK) - Ni Putu Elsy Irawati (Madago Nursing Journal, 2022)
Introduction : Chronic obstructive pulmonary disease (COPD) is a condition in which the lungs experience obstruction that is not fully reversible. One of the independent nursing interventions in dealing with decreased is the diaphragmatic breathing exersice relaxation technique. This technique is a non-pharmacological therapy that can improve abdominal movement by reducing respiratory muscle activity. The purpose of the study was to determine the application of relaxation diaphragmatic breathing to dyspnea in the nursing care of patients with chronic obstructive pulmonary disease (COPD) in Poso Hospital. Research methods: descriptive with a case study approach. Results: obtained complaints of shotness of breath, breathing 27x/m, pulse 102x/m, blood pressure 130/90 mmHg with a diagnosis of ineffective breathing pattern, ineffective airway clearance and activity intolerance. Ventilation support interventions, airway management, and activity therapy. Implementation was carried out for 5 days. Evaluation after the implementation of the implementation of Diaphragmatic Breathing Exersice Relaxation there is change in Dyspnea in Mrs.B. Conclusion the application of Diaphragmatic Breathing Exersice Relaxation can overcome the problem of Dyspnea. Suggestion: are expected to provide nursing interventions to overcome existing nursing problems in Chronic Obstructive Pulmonary Disease (COPD) patients with dyspnea cases.